Pembinaan Pendidikan Agama Islam bagi Mahasiswa Perguruan Tinggi Umum: Studi Kasus di Pondok Pesantren Mahasiswa Al-Jauhar Jember: Islamic Religious Education Development for Students of Public Universities: A Case Study at Al-Jauhar Student Islamic Boarding School, Jember - H. Muchlis (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2008)
Islamic religious education in Indonesian general universities is often limited to only two credits, which is considered insufficient to foster deep understanding and practice of Islamic values among students. This study addresses the gap by exploring how the Al-Jauhar Student Islamic Boarding School in Jember provides supplementary religious education. The research aims to describe the implementation of Islamic religious education coaching for university students, including the reasons they join the pesantren, the teaching system applied, and the challenges faced. A qualitative case study approach was employed, utilizing observation, in-depth interviews, and documentation to collect data from caretakers, administrators, teachers, and students. The findings reveal that students are primarily motivated by the desire to deepen their religious knowledge beyond the minimal university curriculum. The teaching system combines traditional salaf methods (wetonan/bandongan) with modern approaches such as lectures, Q&A, and discussions. Key challenges include students’ limited prior knowledge of Islam and Arabic, scheduling conflicts with university classes, and insufficient facilities. The study concludes that integrated coaching in student pesantren effectively complements formal university education, fostering moral and spiritual foundations, and recommends strengthening institutional cooperation and expanding facilities. Pendidikan agama Islam di perguruan tinggi umum Indonesia seringkali hanya diberikan sebanyak dua sks, yang dinilai kurang memadai untuk menumbuhkan pemahaman dan pengamalan nilai-nilai Islam secara mendalam. Penelitian ini menjawab kesenjangan tersebut dengan mengeksplorasi bagaimana Pondok Pesantren Mahasiswa Al-Jauhar di Jember memberikan pembinaan agama tambahan. Tujuan penelitian ini adalah mendeskripsikan pembinaan pendidikan agama Islam bagi mahasiswa PTU, meliputi alasan mahasiswa masuk pesantren, sistem pengajaran yang diterapkan, serta kendala yang dihadapi. Penelitian menggunakan pendekatan kualitatif dengan rancangan studi kasus, serta teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa motivasi utama mahasiswa adalah keinginan memperdalam ilmu agama karena keterbatasan kurikulum di PTU. Sistem pengajaran yang digunakan merupakan perpaduan antara sistem salaf (wetonan/bandongan) dan sistem modern (ceramah, tanya jawab, diskusi). Kendala yang dihadapi meliputi minimnya dasar pengetahuan agama dan bahasa Arab santri, benturan jadwal dengan perkuliahan, serta kurangnya fasilitas. Penelitian ini menyimpulkan bahwa pembinaan di pesantren mahasiswa secara efektif melengkapi pendidikan formal di PTU dan merekomendasikan penguatan kerja sama institusional serta perluasan fasilitas.